Visualization in the synthetic biology design cycle - Scott-Brown, J (2018)
Synthetic biology is an emerging field with the ultimate aim of designing and building biological systems with particular functions. Achieving this goal requires parallel developments in several areas: experimental methods, libraries of reusable parts mined from natural systems, approaches to mathematical modelling, and design tools. As the biological circuits that are designed and built become more complex, automation becomes increasingly important at every stage.